Christianity for Weak People: How The Holy Spirit Prays for Believers according to Romans 8:26-27 - Agustinus Dermawan (Sekolah Tinggi Teologi Satyabhakti, Malang, 2022)
Abstract For many Christian believers, especially whose family members suffer a prolonged sickness or multiple disease complications, it is often perplexing for them that God seems delaying to answer their prayers. And in many cases, God seems to let those family members to die. How could it be understood? That is not an easy problem to digest for many believers, especially if they think they already serve God in ministry, or churches, or other occasions. Fortunately, there are also comforting words to encourage us in such a perplexing situation, such as Romans 8:26-27, which suggests that the Holy Spirit also do intercession prayers for believers. And these two verses were followed by verse 8:28, where St. Paul concluded that from the previous two verses, we know that God works through everything for good to them that love God. Probably, that is the origin of a famous phrase: “God works often in mysterious ways.” This reflective article is intended to shed light on this old question. Abstrak Bagi banyak orang Kristen, terutama yang anggota keluarganya menderita penyakit yang berkepanjangan atau komplikasi berbagai penyakit, seringkali membingungkan bagi mereka bahwa Tuhan tampaknya menunda untuk menjawab doa-doa mereka. Dan dalam banyak kasus, Tuhan tampaknya membiarkan anggota keluarga itu meninggal. Bagaimana itu bisa dipahami? Itu bukan masalah yang mudah dicerna bagi banyak orang percaya, terutama jika mereka berpikir bahwa mereka telah melayani Tuhan dalam pelayanan, atau gereja, atau kesempatan lainnya. Untungnya, ada juga kata-kata penghiburan untuk mendorong kita dalam situasi yang membingungkan seperti itu, seperti Roma 8:26-27, yang menunjukkan bahwa Roh Kudus juga melakukan doa syafaat bagi orang percaya. Dan kedua ayat ini diikuti oleh ayat 8:28, di mana St. Paulus menyimpulkan bahwa dari dua ayat sebelumnya, kita tahu bahwa Tuhan bekerja melalui segala sesuatu untuk kebaikan bagi mereka yang mengasihi Tuhan. Mungkin, itulah asal mula ungkapan terkenal: “Tuhan sering bekerja dengan cara yang misterius.” Artikel reflektif ini dimaksudkan untuk menjelaskan pertanyaan lama ini.